(3eHOC GSJbdGd GdJhbjYGJ aj GdChQGb GdJLGQjI (B/ s - (3LhQLjJ UHMj YHOg bdjfjs; (3eMehO SejQ GdTQbGhj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1996)
(3JfbSe GdQSGdI Edi bSejf GdbSe GdChd Yf fWGb JWHjb eHOC GSJbdGd GdJhbjYGJ, hGdbSe GdKGfj Yf GdBKGQ GdbGfhfjI GdeJQJHI Ydi eHOC GSJbdGd GdJhbjYGJ(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1996.s
(3HHdjhLQGajG(B: (3UaMGJ(B391-397.s
Keywords: (3eHOC GSJbdGd GdJhbjYGJs; (3GdJLQjOs; (3SMH GdhQbI GdeGdjIs; (3JWgjQ GdOahYs; (3GdTQhW GdGNJjGQjI GdhGQOI HGdhQbI GdJLGQjIs; (3ebGHd GdhaGAs; (3eHOC GSJbdGd GdJhbjYGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1996